2019
DOI: 10.31234/osf.io/sy9fn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Grapsas,Brummelman,Back,Denissen - A Process Model of Narcissistic Status Pursuit - In Press

Abstract: We propose a self-regulation model of grandiose narcissism. This model illustrates an interconnected set of processes through which narcissists (i.e., individuals with relatively high levels of grandiose narcissism) pursue social status in their moment-by-moment transactions with their environments. According to the model, narcissists select situations that afford status. Narcissists vigilantly attend to cues related to the status they and others have in these situations. Based on these perceived cues, narciss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In a rigged video-game tournament, individuals with high narcissism tended to display more status-enhancing behaviors (rank buying) in response to victories and more combative behaviors (point stealing) in response to defeat (Szücs et al, 2022). On an emotional level, more narcissistic individuals displayed greater increases in positive affect after status satisfaction and greater increases in negative affect after status frustration (Grapsas et al, 2021(Grapsas et al, , 2022.…”
Section: Narcissism and Social Statusmentioning
confidence: 99%
“…In a rigged video-game tournament, individuals with high narcissism tended to display more status-enhancing behaviors (rank buying) in response to victories and more combative behaviors (point stealing) in response to defeat (Szücs et al, 2022). On an emotional level, more narcissistic individuals displayed greater increases in positive affect after status satisfaction and greater increases in negative affect after status frustration (Grapsas et al, 2021(Grapsas et al, , 2022.…”
Section: Narcissism and Social Statusmentioning
confidence: 99%
“…Initial studies have already investigated such affective contingencies in narcissistic individuals. On the trait level, Grapsas et al (2022) found that higher scores in admiration and rivalry were related to greater increases in positive affect after satisfaction of the power motive (a motive closely related to social status pursuit) and that higher scores in rivalry were related to greater increases in negative affect. On the daily level, Mota et al (2023) found that status success was related to This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Recent literature on narcissism has suggested that there is a need to assess self-regulatory processes such as wellbeing which might affect behaviors of narcissistic leaders in a social and organizational setting (Grapsas et al 2020). Extant research has been done in the area of narcissism and wellbeing (Wirtz and Riggotti 2020); wellbeing and performance (Bryson et al 2017;Oswald et al 2015; Imran and Shahnawaz 2020; Sakkar Sudha and Shahnawaz 2020) and narcissism and performance (Grijalva et al 2015; Imran and Shahnawaz 2020; Sakkar Sudha and Shahnawaz 2020).…”
Section: Current Studymentioning
confidence: 99%